Starting from an Empty Plate: A Semiotic Study of Instant Noodle Advertisements during the Fasting Month of Ramadan in the Covid-19 Pandemic - Listia Natadjaja (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
From the beginning of the Covid-19 pandemic in 2020 until 2022, Indomie has consistently issued advertisements during the fasting month of Ramadan. During this period, it is a challenge for food manufacturers to promote their products. In the case of Indomie’s advertisement, which started with an idea that visually displays an empty plate and is broadcast during the fasting month, is quite viral because it dares to advertise without displaying the products it sells. Interestingly, Indomie is still holding up empty plates for their advertisement in 2021. The continuity of the story that started with empty plates is what prompted me to continue the analysis of Indomie instant noodle ads that were aired during the fasting months of Ramadan during the pandemic in 2020, 2021, and 2022. The purpose of this research is to reveal the meaning and ideology of what is to be conveyed through these ads. Rolland Barthes' semiotic analysis method is considered suitable to analyze the mythology and ideology behind them. The presence of an empty plate shows the meaning of tolerance for fasting Muslims. Each advertisement describes this form of tolerance differently. Even though it is covered by religious, social, cultural, and economic discourses, the ideology of capitalism is still sensed in all the advertisements that are displayed.